Growing and characterizing one-dimensional crystals within single-walled carbon nanotubes. - Hutchison, J; Sloan, J; Kirkland, A; Green, M (2004)
Single-walled carbon nanotubes (SWNTs) have been used as growth templates for spatially confined crystal growth. The comparative crystallization and high-resolution transmission electron microscopy imaging properties of simple binary halides formed by the alkali iodides MI (M = Li, K, Na, Rb and Cs) within SWNTs are described. The most common structure type observed within SWNTs was the rocksalt archetype, although CsI was observed to form both body-centred cubic (bcc) and rocksalt structure types. ThCl4 was found to form a chain structure of Th[Cl]8 polyhedra. HgI2 crystallized within nanotubes with ultra-narrow (i.e. 0.8 nm) capillaries was observed to form helical 2 x 1 layer crystals.